Strategic approach to the development of ecotourism in Bor District, Serbia - Voza, Danijela; Fedajev, Aleksandra (Hotel and Tourism Management, 2020)
The increase in ecotourism popularity at a global level is a consequence of the increased human concern for the state of natural resources. This type of alternative tourism is increasingly present in tourist trends around the world. For developing countries, ecotourism can be an opportunity for accelerating economic development by exploiting natural resources, without changing their original state. Although it offers great opportunities, the management of tourism in protected or unprotected natural assets is a great challenge. The importance of integrating the actions of all stakeholders and the usage of strategic approach are often neglected. The aim of this paper is to generate strategies for the development of ecotourism in Bor and its surroundings. For this purpose, a combined SWOT-TOWS methodology is applied. Based on the obtained results, nine strategies are proposed, whose implementation would enable the usage of natural and cultural and historical potentials for the revival of ecotourism in this area.